A New Proof of Existence of Positive Weak Solutions for Sublinear Kirchhoff Elliptic Systems with Multiple Parameters. (25th January 2020) - Boulaaras, Salah Mahmoud; Guefaifia, Rafik; Cherif, Bahri; Alodhaibi, Sultan
Abstract : This paper deals with the study of the existence of weak positive solutions for sublinear Kirchhoff elliptic systems with zero Dirichlet boundary condition in bounded domain Ω ⊂ ℝ N by using the subsuper solutions method.